Evaluación del sistema de control interno y su efecto en la toma de decisiones de la empresa Tomonorte, 2018 - Castillo Sandoval, Geraldine Yajaira (2022)
The purpose of this research is to establish the effect of the evaluation of the Internal Control System in the decision making of the Tomonorte Company in 2018. The design is non-experimental, cross-sectional, correlational, it seeks to find out the relationship between the dependent and independent variable. Both the population and the sample is formed by 48 collaborators of the Tomonorte Company. Likewise, the technique applied is the survey and the instrument used is the questionnaire to collect the information; therefore, the data obtained were processed in the SPSS statistical software. It is concluded that there is a direct and significant effect between internal control and decision making of Tomonorte, 2018 with a significance level of 0.000<0.05 it is shown that for the Rho Spearman statistical test a value of p=0.801 was obtained which indicates that there is a high positive correlation between the variables Internal control and Decision making. It is recommended to the General Management to carry out the proposed activities in order to improve the administrative, economic and financial results and human resources.